KAJIAN YURIDIS TERHADAP PERBUATAN SESEORANG YANG MELAKUKAN PENCURIAN DENGAN KEKERASAN DALAM PERSPEKTIF KUHP (Studi Putusan 2964/Pid. B/2019/PN. Mdn) - Mulyoto, Mulyoto; Purba, Nelvitia; Sahlepi, Arief (Jurnal Ilmiah METADATA, 2021)
The crime of theft with violence is regulated in Article 365 of the Criminal Code, which consists of 4 (four) paragraphs. Each paragraph in the article determines criminal elements that are different from the main criminal form (Article 362 of the Criminal Code), namely the existence of additional criminal conditions and elements, so that the criminal threat becomes more severe. The criminal responsibility of the perpetrators of the crime of theft with violence based on the Criminal Code, namely the fulfillment of the criminal elements as stipulated in Article 362 of the Criminal Code as the main form of the crime of theft, which is then filled with conditions or other additional criminal elements as a reason for the aggravation of the crime in the crime theft. The basis for the judge's consideration in making a decision against the perpetrator of the crime of theft with violence, namely by considering the charges of the public prosecutor, or what is called juridical considerations, as well as considering things that are aggravating and mitigating for the defendant.